2019
DOI: 10.1161/atvbaha.119.313348
|View full text |Cite
|
Sign up to set email alerts
|

Force Sensing by Piezo Channels in Cardiovascular Health and Disease

Abstract: Mechanical forces are fundamental in cardiovascular biology, and deciphering the mechanisms by which they act remains a testing frontier in cardiovascular research. Here, we raise awareness of 2 recently discovered proteins, Piezo1 and Piezo2, which assemble as transmembrane triskelions to combine exquisite force sensing with regulated calcium influx. There is emerging evidence for their importance in endothelial shear stress sensing and secretion, NO generation, vascular tone, angiogenesis, atherosclerosis, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
166
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(168 citation statements)
references
References 103 publications
1
166
0
1
Order By: Relevance
“…(ii) Piezo1-mediated depolarization in SMCs activates voltage-operated calcium influx and vasoconstriction whereas TRPV4 -mediates vasodilation (92), and (iii) TRPV1 mediates contraction whereas TRPV4 mediates dilation of the ciliary muscle (93). We propose that Piezo1 and TRPV4 channels in TM cells are coupled to distinct microdomains and/or downstream Ca 2+ effectors.…”
Section: Discussionmentioning
confidence: 88%
“…(ii) Piezo1-mediated depolarization in SMCs activates voltage-operated calcium influx and vasoconstriction whereas TRPV4 -mediates vasodilation (92), and (iii) TRPV1 mediates contraction whereas TRPV4 mediates dilation of the ciliary muscle (93). We propose that Piezo1 and TRPV4 channels in TM cells are coupled to distinct microdomains and/or downstream Ca 2+ effectors.…”
Section: Discussionmentioning
confidence: 88%
“…These are known as Piezo channels, and they are blocked by GsMTx-4 and Gd 3+ (Coste et al 2010). The channels are widely expressed and are important to the normal function of multiple tissues, including from the cardiovascular system (Beech and Kalli 2019). The channels display rapid voltagedependent inactivation in patch-clamped and whole-cell mechanical assays (Coste 2012;Coste et al 2010;Murthy et al 2017;Wu et al 2017).…”
Section: Stretch-activated Nonspecific Cation Channelsmentioning
confidence: 99%
“…The molecular and functional studies required to test these ideas will take time to complete. Moreover, our studies have shown the importance of understanding PIEZO1 in its native membrane environment because the native endothelial and red blood cell environments profoundly alter the gating characteristics of PIEZO1 18,27,44,45 . We do not yet know whether endothelial cell dysfunction affects the properties of PIEZO1, but any changes could be relevant to COVID-19 and its progression to fatality.…”
Section: Discussionmentioning
confidence: 93%